2019
DOI: 10.1186/s12877-019-1213-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of an evaluation tool for geriatric rehabilitation care

Abstract: Background Geriatric rehabilitation care (GRC) is short-term and multidisciplinary rehabilitation care for older vulnerable clients. Studies were conducted about its effects. However, elements that influence the quality of GRC have not been studied previously. Methods In this study realist evaluation is used to find out which are the mechanisms and outcomes and which (groups of) persons are the context for GRC, according to GRC professionals. The mechanisms, outcomes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The second case was based on an evaluation tool for geriatric rehabilitation care (Janssen et al, 2019). This tool offers multidisciplinary NH care teams insight into the quality of their geriatric rehabilitation care and areas for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…The second case was based on an evaluation tool for geriatric rehabilitation care (Janssen et al, 2019). This tool offers multidisciplinary NH care teams insight into the quality of their geriatric rehabilitation care and areas for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…They found that patient goal engagement improved significantly between admission and discharge. In addition, the evaluation tool for geriatric rehabilitation, developed by Janssen et al (2019), confirms the appropriateness of working with small goals. Two of the evaluation tools’ criteria are “Rehabilitation goals are continuously coordinated with the client” and “Informal caregivers are explicitly involved in the therapy and are aware that they can practice with the client.”…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, scientific knowledge is often not immediately applicable into care practice. Therefore, we started and will continue to translate our knowledge in co-creation with older persons, care professionals and researchers into practical tools and working methods that can be implemented in care practice (Haufe et al, 2019;Janssen et al, 2019).…”
Section: Future Directionsmentioning
confidence: 99%